2017
DOI: 10.15171/apb.2017.058
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Capped with Silver Nanoparticles as an Antibacterial Agent against Multi-Drug Resistance Bacteria

Abstract: Purpose: Many antimicrobial medications are available to combat infections. However, the indiscriminate use of antibiotics has produced antibiotic resistance in the case of many bacterial pathogens. This study focuses on the development of nanoparticles (NPs) that enhance the in vitro antibiotic activity of vancomycin against multi-drug resistant (MDR) organisms.Methods: Spherical shaped thioglycolic acid-stabilized silver nanoparticles (TGA-AgNPs) were prepared by using a simple chemical reduction method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 12 publications
1
44
1
Order By: Relevance
“…Besides the broad-spectrum antibacterial properties that NPs have against Gram-positive and -negative bacteria, NPs have been used as vectors for the delivery of antimicrobial moieties that greatly improve their biocidal properties (Beyth et al, 2015 ; Rai A. et al, 2016 ; Singh J. et al, 2016 ; Esmaeillou et al, 2017 ; Wang et al, 2017a ; Zaidi et al, 2017 ; Hadiya et al, 2018 ). Some of the advantages of using NPs as vectors are due to their small and controllable size; their protective action against enzymes that would otherwise destroy antimicrobial compounds; their ability to actively deliver antibiotics; and their capability to combine several therapeutic modalities onto a single nanomaterial ( e.g ., several antibiotics/compounds onto the same NPs for combined action; combining silencing agents and drugs, etc.)…”
Section: Nanomaterials Against Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the broad-spectrum antibacterial properties that NPs have against Gram-positive and -negative bacteria, NPs have been used as vectors for the delivery of antimicrobial moieties that greatly improve their biocidal properties (Beyth et al, 2015 ; Rai A. et al, 2016 ; Singh J. et al, 2016 ; Esmaeillou et al, 2017 ; Wang et al, 2017a ; Zaidi et al, 2017 ; Hadiya et al, 2018 ). Some of the advantages of using NPs as vectors are due to their small and controllable size; their protective action against enzymes that would otherwise destroy antimicrobial compounds; their ability to actively deliver antibiotics; and their capability to combine several therapeutic modalities onto a single nanomaterial ( e.g ., several antibiotics/compounds onto the same NPs for combined action; combining silencing agents and drugs, etc.)…”
Section: Nanomaterials Against Bacteriamentioning
confidence: 99%
“…Some of the advantages of using NPs as vectors are due to their small and controllable size; their protective action against enzymes that would otherwise destroy antimicrobial compounds; their ability to actively deliver antibiotics; and their capability to combine several therapeutic modalities onto a single nanomaterial ( e.g ., several antibiotics/compounds onto the same NPs for combined action; combining silencing agents and drugs, etc.) (Turos et al, 2007 ; Huh and Kwon, 2011 ; Mohammed Fayaz et al, 2011 ; Liu et al, 2013 ; Qi et al, 2013 ; Li et al, 2014 ; Ranghar et al, 2014 ; Thomas et al, 2014 ; Wang et al, 2014 ; Payne et al, 2016 ; Rai A. et al, 2016 ; Singh J. et al, 2016 ; Yeom et al, 2016 ; Esmaeillou et al, 2017 ; Zaidi et al, 2017 ; Zong et al, 2017 ; Hadiya et al, 2018 ).…”
Section: Nanomaterials Against Bacteriamentioning
confidence: 99%
“…These bactericidal pathways help the nanomaterials to overcome the antibiotic-resistant mechanism. Esmaeillou et al (2017), demonstrated that the silver nanoparticles could overcome the vancomycin-resistant in cases of S. aureus through binding with the vancomycin and enhancing bacterial cell death. Also, Saeb et al (2014), reported that silver nanoparticles could avoid the methicillin-resistant in cases of S. aureus through binding with the antibiotic.…”
Section: Enhanced Antibacterial Activity Against Resistant S Aureusmentioning
confidence: 99%
“…The antimicrobial activity of our synthesized PVP-AgNPs is comparable to other reported in different studies, using similar culture conditions. MIC values in the literature range from 0.8 µg mL -1 to 13.5 µg mL -1 for S. aureus (Table S1, supplementary material) (13,28), and from 0.4 µg mL -1 to 40 µg mL -1 for C. albicans (Table S2, supplementary material) (29,30). The physicochemical properties of AgNPs depend upon their morphology and capping agent; yet different AgNPs with different traits may display close antimicrobial activity (19).…”
Section: Resultsmentioning
confidence: 99%